PRE-CLINICAL EVALUATION OF EXTRACTS AND ESSENTIAL OILS FROM BETEL-LIKE SCENT PIPER SPECIES IDENTIFIED POTENTIAL CANCER TREATMENT - Sanubol, Arisa; Chaveerach, Arunrat; Tanee, Tawatchai; Sudmoon, Runglawan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Nine Piper species with betel-like scents are sources of industrial and medicinal aromatic chemicals, but there is lack of information on cytotoxicity and genotoxicity for human safety, including how these plants impact human cervical cancer cell line. Methods: Plant leaves were extracted with hexane and hydro-distilled for essential oils. The extracts and oils were preclinically studied based on cyto - and genotoxicity using microculture tetrazolium (MTT) and comet assays. Results: The crude extracts showed an IC50 in leukocytes and HeLa cells of 58.59 -97.31 mg/ml and 34.91-101.79 mg/ml, the LD50 is higher than 5000 mg/kg. With lower values than the crude extracts, the essential oils showed an IC50 in leukocytes and HeLa cells of 0.023-0.059 μg/ml and 0.025-0.043 μg/ml, the LD50 is less than 50 mg/kg. IC50 values showed that the essential oils were highly toxic than the crude extracts. At the level of human genetic materials, the crude extracts of two species, including P. betloides and P. crocatum, showed a significant toxicity (p < 0.05) in leukocytes. The other samples were non-toxic. The crude extracts of all samples showed significant genotoxicity in HeLa cells. The essential oils of all studied Piper species showed insignificant toxicity in leukocytes. For HeLa cells, the eight-studied species showed significant toxicity in HeLa cells, whereas only P. submultinerve showed insignificant toxicity. Conclusion: The crude extracts and essential oils should be tested as putative cervical cancer treatments due to less toxicity in human normal cells.